PENERAPAN STRATEGI PEMASARAN DAN AKSESIBILITAS RUMAH TANGGA TERHADAP BIHUN TAPIOKA DI KOTA METRO - Bazai, Fadhilah Ismi; Sayekti, Wuryaningsih Dwi; Lestari, Dyah Aring Hepiana (Jurnal Ilmu-Ilmu Agribisnis, 2017)
This research aimed to study the owners understanding of marketing strategy of tapioca vermicelli, analyze the implementation of marketing strategy that has been done, and know the accessibility of consumers to obtain tapioca vermicelli.Â  This research used a case study method at Sinar Harapan (SH) and Bintang Obor (BO) Agroindustries. Respondents were the owners of agroindustries, distributors, and consumers of tapioca vermicelli.Â  Research data was analyzed by a descriptive statistical analysis (level of understanding through an all-round management approach and accessibility of consumers) and qualitative descriptive (the realization of marketing strategy that has been done).Â  The results showed that tapioca vermicelliâs producers at Metro City were quite understood the marketing strategy, but their implementation were not in accordance with their understanding.Â  The owner of BO considered more understood the importance of marketing strategy compared to the owner of SH.Â  The implementation of marketing strategy by SH and BO producers were almost the same.Â  The difference of these two agroindustries were that the BO implemented the price reserve strategy while SH did not.Â  Accessibility of consumers to obtained tapioca vermicelli was easy.Key words: accessibility, marketing strategy, tapioca vermicelli